Pengaruh Harga Pokok Produksi (HPP) terhadap Laba Bersih Pabrik Minyak Goreng Kemasan Tahun 2022-2023 - Marbun, Janri; Fathimah, Vidya (Jurnal Informatika Ekonomi Bisnis, 2024)
The research aims to determine the effect of production costs on net profit. This study was carried out by considering fluctuations in production costs as well as increases and decreases in net profit for the period 2022 to 2023 This research is quantitative research. The population of this research consists of all financial reports of PT. Permata Hijau Palm Oleo Belawan and this research is financial reports for a year from 2022 to 2023. The data source for this research is secondary data. The processed with SPSS verion 25 software. The results of simple linear regression analysis show Y = -72454.130 + 0.868X. Meanwhile, the results of the of the t test show that production costs partially have a positive and signigicant effect on the net profit of the PT. Permata Hijau Palm Oleo Belawan. This is proven by tcount 6,786 > ttable 1,71387. This means that H0 is rejected and Ha is accepted. The coefficient of determination test (R2) was 67,7% dan 32,3% respectively, but was influenced by other factors not discussed in this study.